Citrus aurantium Peel Extract Combined with Doxorubicin-Induced ROS-driven Cell Cycle Arrest and Apoptosis of Triple-Negative Breast Cancer Cells - Suzery, Meiny; Amalina, Nur Dina; Cahyono, Bambang (Open Access Macedonian Journal of Medical Sciences, 2023)
The current approach to breast cancer has problems with the emergence of resistance, side effects, and even the emergence of post-therapy relapses. One of the reasons is that the available chemotherapy is still based on cytotoxicity through cell cycle inhibition and apoptosis induction. In fact, there are still several mechanisms for the direction of cytotoxicity to become more prospective targets of chemotherapy action, such as reactive oxygen species (ROS) leading to cell death induction. One prospective candidate from natural ingredients is Citrus aurantium peel extract (CSP). This study aims to develop a CSP as a co-chemotherapy candidate that leads to aging induction and ROS modulation in breast cancer cells. The breast cancer cell model used is triple-negative breast cancer cells (TNBC), which is a highly metastatic cell model. Apoptosis and cell cycle modulation profiles were analyzed under PI-Annexin and PI flow cytometry, respectively. The ROS level was evaluated under DCFDA flow cytometry. The combination of CSP and Dox induces oxidative stress with ROS levels up to 3.5 times. The increase in ROS levels was in line with the dose-dependent induction of apoptosis and induced G2/M phase cell cycle arrest. Taken together, CSP potentially induces the Dox effect on MDA-MB-231 cells, which may be mediated by the elevation of the ROS levels leading to cell death induction.